2013
DOI: 10.1093/ajh/hpt209
|View full text |Cite
|
Sign up to set email alerts
|

Nativity, Language Spoken at Home, Length of Time in the United States, and Race/Ethnicity: Associations with Self-Reported Hypertension

Abstract: Race/ethnicity modifies the relationship between acculturation-related factors and hypertension. Consideration of disease prevalence in origin countries is critical to understanding health patterns in immigrant populations. Validation of self-reported hypertension in Hispanic populations is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 26 publications
3
32
1
Order By: Relevance
“…For example, black people who are foreign-born have lower body mass indexes (21) and lower rates of diabetes (22), self-reported high blood pressure (11), and allostatic load (13) than their US-born counterparts. Particularly with regard to hypertension, a largely asymptomatic condition, these findings may be affected by awareness of one’s condition, which is in turn a reflection on prior health care use and experience and other social determinants of health known to vary by nativity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, black people who are foreign-born have lower body mass indexes (21) and lower rates of diabetes (22), self-reported high blood pressure (11), and allostatic load (13) than their US-born counterparts. Particularly with regard to hypertension, a largely asymptomatic condition, these findings may be affected by awareness of one’s condition, which is in turn a reflection on prior health care use and experience and other social determinants of health known to vary by nativity.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent New York City survey, US residency for ≥10 years was associated with higher self-reported HTN prevalence in Blacks and Hispanics [8]. There is significant heterogeneity among Hispanics by racial admixture, country of origin, CVD risks, and disease prevalence; age-adjusted HTN rates appear higher among Puerto Ricans and Dominicans as compared with Mexican-Americans and Cubans [9,10].…”
Section: Introductionmentioning
confidence: 94%
“…The most common form, hypertension or high blood pressure, is highly prevalent in minority population groups, particularly Blacks (Yi, Elfassy, Gupta, Myers, & Kerker, 2014). However, some researches have shown that recent African migrants are less likely to develop high blood pressure after controlling for age and obesity factors than their counterparts, African Americans (Okwuosa & Williams, 2012).…”
Section: African Transnational Migrants and High Blood Pressurementioning
confidence: 99%
“…Scholars in the past have focused more on the gender-specific engagement of resources and the culturally relevant perspectives of health, primarily for women (Gastaldo, Gooden, & Massaquoi, 2005;Messias, 2002). In the study of high blood pressure specifically, behaviors in daily life activities serve as potentially exacerbating or preventative factors for high blood pressure (McAlister, Lewanczuk, & Teo, 1996;Reddy & Katan, 2004;Yi et al, 2014). These include diet, level of physical activity, familial history, and stress-causing interactions.…”
Section: Multinational Ties and Health Outcomesmentioning
confidence: 99%